2009
DOI: 10.1177/0960327109104528
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling in rat liver treated with compounds inducing elevation of bilirubin

Abstract: We have constructed a large-scale transcriptome database of rat liver treated with various drugs. In an effort to identify a biomarker for the diagnosis of elevated total bilirubin (TBIL) and direct bilirubin (DBIL), we extracted 59 probe sets of rat hepatic genes from the data for seven typical drugs, gemfibrozil, phalloidin, colchicine, bendazac, rifampicin, cyclosporine A, and chlorpromazine, which induced this phenotype from 3 to 28 days of repeated administration in the present study. Principal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…A previous study had reported that the infl ammatory response, highlighted by Group 1 compounds in the present study, could cause cholestasis through indirect inhibition of BSEP (Hartmann et al, 2002). The lipid metabolism pathway highlighted by Group 2 (Table 2) could be associated with bilirubin upregulation (Hirode et al, 2009). In addition, cholestasis has been reported to contribute to dysfunction of cholesterol biosynthesis (Nemes et al, 2016).…”
Section: Discussionmentioning
confidence: 48%
“…A previous study had reported that the infl ammatory response, highlighted by Group 1 compounds in the present study, could cause cholestasis through indirect inhibition of BSEP (Hartmann et al, 2002). The lipid metabolism pathway highlighted by Group 2 (Table 2) could be associated with bilirubin upregulation (Hirode et al, 2009). In addition, cholestasis has been reported to contribute to dysfunction of cholesterol biosynthesis (Nemes et al, 2016).…”
Section: Discussionmentioning
confidence: 48%
“…Zidek et al (7) reported high accuracy with a 64-gene classifier for the prediction of acute hepatotoxicity. The Toxicogenomics Project in Japan, set up by the Ministry of Health, Labour and Welfare, National Institute of Health Sciences, and 15 pharmaceutical companies, has also identified several toxicogenomic signatures indicative of the various toxic modes of action such as phospholipidosis (8), glutathione depletion (9), bilirubin elevation (10), non-genotoxic hepatocarcinogenesis (11), and peroxisome proliferation (12). …”
Section: Introductionmentioning
confidence: 99%
“…The purpose of TGP2 was to identify biomarkers for diagnosing and/or predicting compound toxicity based upon the gene expression data accumulated in TGP1. A number of biomarkers and gene expression profiles indicative of exposure to particular toxic compounds were reported following the TGP1 and TGP2 studies (Kiyosawa et al, 2006;Morishita et al, 2006;Tamura et al, 2006aTamura et al, , 2006bKiyosawa et al, 2007;Omura et al, 2007;Hirode et al, 2008Hirode et al, , 2009aHirode et al, and 2009bUehara et al, 2008aUehara et al, , 2008bUehara et al, and 2008cKondo et al, 2009;Minowa et al, 2012). Prior to use of the gene expression data accumulated during TGP1 in future drug discovery studies, the procedures used to analyze gene expression must be validated and the degree of inter-laboratory variation must be assessed.…”
Section: Introductionmentioning
confidence: 99%